Process intensification of silica amination through ultrasound-assisted impregnation: toward highly efficient amino-functionalized particles - Hendrix Abdul Ajiz; Widiyastuti Widiyastuti; Heru Setyawan; Ade Sonya Suryandari; Nove Kartika Erliyanti (Konversi, 2026)
Amine-functionalized porous silica is a highly promising material for sustainable carbon capture; however, increasing amine loading is often limited by pore blocking and diffusion resistance of the modifying agents. This study proposes an ultrasound-assisted ex-situ impregnation strategy to enhance aminopropyl grafting efficiency within macroporous silica matrices. Macroporous silica particles were synthesized via a sol-gel spray drying route using an anionic surfactant template and subsequently functionalized with alkoxy-aminopropyl ligands. The results demonstrate that the synergistic effects of ultrasonic irradiation and macroporous morphology significantly improve ligand distribution homogeneity, suppress particle agglomeration, and promote aminopropyl penetration into the internal pore network while minimizing pore blocking induced by self-condensation. FTIR and TG-DTA analyses confirm a substantial increase in aminopropyl loading up to 0.9610 mmol g-1 silica, nearly twice that achieved by conventional impregnation, despite a reduction in specific surface area due to pore filling. Overall, this approach provides an efficient and scalable pathway for producing amine-rich silica adsorbents with enhanced accessibility and strong potential for sustainable CO2 capture applications.